2011
DOI: 10.1007/s13238-011-1071-9
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2 acts upstream of mitochondrial permeability transition during paclitaxel-induced apoptosis

Abstract: Sequential activation of cyclin-dependent kinases (Cdks) controls mammalian cell cycle. Here we demonstrate that the upregulation of cyclin-dependent kinase 2 (Cdk2) activity coincides with the loss of mitochondrial membrane potential (MMP) in paclitaxel-induced apoptosis. Ectopic expression of the dominant negative Cdk2 (Cdk2-dn) and a specific Cdk2 inhibitor, p21 WAF1/CIP1 , effectively suppresses the loss of MMP, the release of cytochrome c, and subsequent activation of caspase-3 in paclitaxel-treated cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…After cisplatin induction, CDK2 kinase activity is activated, mostly by the up-regulation of its cofactor cyclin A, but its inhibition by kenpaullone or CDK2 KO results in reduced mitochondrial ROS production and reduced caspase-3/7–mediated activation of apoptosis. Our results are consistent with previous studies that CDK2 activation is required for the disruption of mitochondrial permeability in apoptosis by various insults in the kidney, thymus, and liver ( Jin et al, 2003 ; Granés et al, 2004 ; Guo et al, 2011 ; Megyesi et al, 2016 ; Seng et al, 2016 ). An unpublished study has reported that the inhibition of CDK2 is also protective against antibiotic ototoxicity in the cochlea ( Tao, 2014 ), further supporting our conclusion that CDK2 inhibition protects against hearing loss caused by diverse ototoxic insults.…”
Section: Discussionsupporting
confidence: 94%
“…After cisplatin induction, CDK2 kinase activity is activated, mostly by the up-regulation of its cofactor cyclin A, but its inhibition by kenpaullone or CDK2 KO results in reduced mitochondrial ROS production and reduced caspase-3/7–mediated activation of apoptosis. Our results are consistent with previous studies that CDK2 activation is required for the disruption of mitochondrial permeability in apoptosis by various insults in the kidney, thymus, and liver ( Jin et al, 2003 ; Granés et al, 2004 ; Guo et al, 2011 ; Megyesi et al, 2016 ; Seng et al, 2016 ). An unpublished study has reported that the inhibition of CDK2 is also protective against antibiotic ototoxicity in the cochlea ( Tao, 2014 ), further supporting our conclusion that CDK2 inhibition protects against hearing loss caused by diverse ototoxic insults.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that cyclin A-Cdk2 activity is required for apoptosis induced by diverse stimuli [3] [9] . Because cyclin A-Cdk2 is a protein kinase, we considered the possibility that it mightpromote apoptosis by directly phosphorylating and thereby activating a component of the cell death regulatory machinery.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that cyclin A-Cdk2 also plays an importantrole in apoptosis. Cdk2 activation has been observed inthe apoptosis ofultraviolet irradiatedmesangial cells [3] , etoposide-treatedhuman leukemic cells [4] , [5] , growth factor-deprived HUVEC cells [6] , ginsenoside-Rh2 (G-Rh2)-treated human hepatomacells [7] , panaxadiol-treated SK-HEP-1 cells [8] , and paclitaxel-treated HeLa cells [9] . We showed previously that Cdk2 activity, but notCdc2 activity, was selectively up-regulated and that this up-regulation wasrequired for the induction of apoptosis by G-Rh2 [7] , panaxadiol [8] , or etoposide [4] in several cancer celllines, including SK-HEP-1 cells and HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK2 is predominantly located in the nucleus, regulates progression of cells from G 1 to S phase and has been reported to be a protein closely associated with cell apoptosis. CDK2 is able to alter the permeability of the mitochondrial membrane and thus activate caspase 3 and Bax, in addition to suppressing Bcl-2 to increase cellular apoptosis (45)(46)(47)(48)(49). Sun et al (50) demonstrated that PKC-δ may mediate cellular apoptosis by regulating cyclins.…”
Section: Discussionmentioning
confidence: 99%